2022
DOI: 10.1002/rai2.12048
|View full text |Cite
|
Sign up to set email alerts
|

lncRNA X‐inactive‐specific transcript is a potential biomarker related to changes in CD4+ T cell levels in systemic lupus erythematosus

Abstract: BackgroundSystemic lupus erythematosus (SLE) is a particularly heterogeneous autoimmune disease. This study was intended to clarify the correlations between X‐inactive‐specific transcript (XIST) expression and SLE clinical features and the contribution of XIST to SLE pathogenesis at the transcriptome level.MethodsXIST expression in 79 SLE patients, 14 rheumatoid arthritis patients, and 23 healthy controls was determined by quantitative polymerase chain reaction. The Benjamini and Hochberg adjusted method and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Recently, high-expression of XIST in CD4-positive cells and natural killer cells has been suggested to trigger the proliferation of naïve CD4 (+) T cells in primary biliary cholangitis ( 30 ). In another study, high XIST expression has been found to be associated with the CD4-positive T cell level in systemic lupus erythematosus patients ( 31 ).…”
Section: Discussionmentioning
confidence: 92%
“…Recently, high-expression of XIST in CD4-positive cells and natural killer cells has been suggested to trigger the proliferation of naïve CD4 (+) T cells in primary biliary cholangitis ( 30 ). In another study, high XIST expression has been found to be associated with the CD4-positive T cell level in systemic lupus erythematosus patients ( 31 ).…”
Section: Discussionmentioning
confidence: 92%
“…Ghafouri-Fard et al found that in stage III immature T cells, Thymic T lymphocyte-natural cytotoxicity triggering Receptor 1 (Thy-ncR1) activates the adjacent surface differentiation antigen CD gene cluster by degrading mRNA-Microfibril Associated Protein 4 (MFAP4), indicating that lncRNAs are involved in the differentiation and maturation of T cells [14] . Liu et al found that lncRNA may affect the activation of T cells and the proliferation of CD4 + and CD8 + cells by inhibiting miRNA [15,16] . Another study found that silencing lncRNA-Antisense Non-coding RNA in the Inhibitor of the cyclin D-dependent kinases (INK4) Locus (ANRIL) can inhibit the activation of T cells [17] .…”
Section: And Figmentioning
confidence: 99%